The Effectiveness of Transfer Pricing in Multinational Corporations : A Global Perspective - Abdellah Benhabib; Khalid Benali; Mohamed Tkiouat (Harmoni Economics: International Journal of Economics and Accounting, 2024)
Transfer pricing remains a critical issue in international taxation, particularly for multinational corporations (MNCs). This paper assesses the effectiveness of transfer pricing mechanisms in managing intercompany transactions and ensuring compliance with international tax regulations. By reviewing case studies of large MNCs and conducting a cross-country comparison, the research evaluates the impact of transfer pricing rules on corporate profitability, tax avoidance, and the role of accountants in mitigating risks. The findings suggest that while transfer pricing helps MNCs optimize tax liabilities, it also raises ethical and transparency concerns that require stronger regulatory oversight.